Trivial, Interesting, or Overselling? The Microbiome and "What It Means to Be Human". (3rd March 2021) - Parke, Emily C
Abstract: Discussions of microbiome research increasingly refer to the microbiome's impact on what it means to be human. These claims are rarely carefully explained or justified. Given the increasing importance of microbiome research across the life sciences, philosophy, and the public sphere, it is worth exercising more care in these discussions. This article offers a guide for doing so. There are many different ways to interpret the details of ambiguous claims about the microbiome and what it means to be human. I discuss some possible interpretations and show how the resulting claims can range from trivial to suggestive of interesting research to controversial and overhyped. I recommend greater caution and clarity in ongoing discussions of microbiome research and its implications.